Burnout among Occupational Therapists in Portugal: A Study of Specific Factors. - Reis, Helena I. S.; Vale, Catarina; Camacho, Catarina; Estrela, Cátia; Dixe, Maria dos Anjos (Occupational Therapy in Health Care, 2018)
This pilot study was conducted using a sample of 374 Portuguese occupational therapists to evaluate burnout levels and prevalence among occupational therapists as well as to relate those levels to practitioner age, gender, client age, years of professional activity, and area of practice. The Copenhagen Burnout Inventory questionnaire (Portuguese version) and a sociodemographic questionnaire was used. Results showed that ∼23%, 44%, and 45% of occupational therapists presented with client-related burnout, personal burnout (PB), and work-related burnout, respectively. Higher rates of burnout were observed across all dimensions as the age of the professionals increased, with more years of working increased the client-rated rate, and client age increased the PB rate. Outcomes suggest a need to implement intervention programs to promote personal and organizational strategies to prevent burnout.